Shapeshifting subjects : Gloria Anzaldúa's naguala and border arte - Zaytoun, Kelli D., 1964- (Transformations (University of Illinois (System). Press), 2022)
"Scholars have long cited Gloria Anzaldúa to make or support claims about selfhood. But many people overlook her emphasis on la naguala and her cutting-edge contribution to subjectivity. Kelli D. Zaytoun draws on Anzaldúa's thought to present a radically inclusive and expansive approach to selfhood, creativity, scholarship, healing, coalition-building, and activism. Zaytoun focuses on Anzaldúa's la naguala/the shapeshifter, a term borrowed from nagualismo. This groundbreaking theory of subjectivity details a dynamic relationship between "inner work" and "public acts" that strengthens the role of individuals in social and transformative justice work. Zaytoun's detailed emphasis on la naguala, and Nahua metaphysics specifically, brings much needed attention to Anzaldúa's long-overlooked contribution to the study of subjectivity. The result is a women and queer of color/feminist-focused work aimed at scholars in many disciplines and intended to overcome barriers separating the academy from everyday life and community"--